Drug repurposing from the perspective of pharmaceutical companies. (18th May 2017) - Cha, Y; Erez, T; Reynolds, I J; Kumar, D; Ross, J; Koytiger, G; Kusko, R; Zeskind, B; Risso, S; Kagan, E; Papapetropoulos, S; Grossman, I; et al.
Abstract : Drug repurposing holds the potential to bring medications with known safety profiles to new patient populations. Numerous examples exist for the identification of new indications for existing molecules, most stemming from serendipitous findings or focused recent efforts specifically limited to the mode of action of a specific drug. In recent years, the need for new approaches to drug research and development, combined with the advent of big data repositories and associated analytical methods, has generated interest in developing systematic approaches to drug repurposing. A variety of innovative computational methods to enable systematic repurposing screens, experimental as well as through in silico approaches, have emerged. An efficient drug repurposing pipeline requires the combination of access to molecular data, appropriate analytical expertise to enable robust insights, expertise and experimental set‐up for validation and clinical development know‐how. In this review, we describe some of the main approaches to systematic repurposing and discuss the various players in this field and the need for strategic collaborations to increase the likelihood of success in bringing existing molecules to new indications, as well as the current advantages, considerations and challenges in repurposing as a drug development strategy pursued by pharmaceutical companies. Linked Articles: This article is part of a themed section on Inventing New Therapies Without Reinventing the Wheel: The Power of Drug Repurposing. To view the other articles in this section visithttp://onlinelibrary.wiley.com/doi/10.1111/bph.v175.2/issuetoc